Fluorescence-guided biopsy in tile diagnosis of an unknown primary cancer in patients with metastatic cervical lymph nodes - Boonchu Kulapaditharom (2018)
This study was conducted to determine the effectiveness of fluorescence- guided biopsy in diagnosis of unknown primary cancers in the head and neck. Thirteen patients with biopsy-proven cervical node metastases were evaluated prospectively with laser-induced fluorescence (LIF) endoscopy in parallel to panendoscopy. Among the 13 positive sites suggested by LIF imaging, 5 were confirmed by histopathology as squamous cell carcinoma, 4 as dysplasia, 2 as inflammation, and 2 as normal. Panendoscopy with random biopsies located 2. The 2 cases of squamous cell carcinomas discovered conventionally were identified by histologic sections from ipsilateral tonsillectomy. In this series, the unknown primary cancers were localized by LIF imaging and conventional means at rates of 38.5% and 15.4%, respectively. The LIF imaging not only aided in revealing a greater proportion of occult primary cancers, but also helped in reducing the number of unnecessary biopsies. Fluorescence- guided biopsy diagnosis provides useful information for therapeutic planning with curative aim or for adequate palliation.